Purpose matters : Impact of public loan guarantees on business growth - Kotamäki, Mauri (Elsevier, 2026)
This study investigates the impact of public bank loan guarantees on firm performance in Finland, a small and open economy, leveraging a novel empirical approach and detailed financial instrument analysis. We combine registry-based data with records from Finnvera, Finland’s National Promotional Bank, and apply the cutting-edge panel matching methodology of Imai et al. (2023) to address causal inference challenges in this context. Our results reveal that guarantees significantly boost turnover, employment, and total assets, with effects varying by loan purpose. Notably, guarantees tied to intangible investments yield the strongest growth in turnover and employment, alongside substantial asset expansion, a granularity often overlooked in prior studies. While average productivity effects are near zero, we uncover tentative evidence of positive productivity gains for intangible capital guarantees. Further disaggregation highlights amplified impacts among micro-enterprises, offering fresh insights into the heterogeneity of policy outcomes. These findings advance our understanding of public financial instruments’ role in fostering economic growth at a nuanced level.